2019
DOI: 10.35463/j.apr.2019.01.02
|View full text |Cite
|
Sign up to set email alerts
|

The Lower Cretaceous Tirgan Formation in the Gelian Section (Kopet Dagh, North Iran): Microfacies, Microfossils, and Their Biostratigraphic Significance

Abstract: The carbonate succession of the Tirgan Formation was studied in the Gelian section located 25 km south of Shirvan town (central Kopet Dagh). In this section, the Tirgan Formation contains a rich assemblage of calcareous algae and foraminifera. Based mainly on the orbitolinid association a latest Barremian-ealy Aptian age was assigned to the Tirgan Formation in the Gelian section. Based on the available stratigraphic analyses and age assignments of the overlying Sarcheshmeh Formation by different authors, one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The two sections (axial and transverse) from the Taft Formation are here assigned to Iraqia simplex Henson, a taxon restricted to the late early Aptian to basal upper Aptian (Ullastre et al, 2002;Masse, 2003;Schlagintweit et al, 2016). It has previously been recorded from the lower Aptian Taft (Schlagintweit et al, 2019) and Tirgan formations (e.g., Bucur et al, 2019). The specimen determined as Mesorbitolina parva (Douglass) by Gheiasvand et al (2019, fig.…”
Section: Taft Formation Of Central Iranmentioning
confidence: 95%
See 1 more Smart Citation
“…The two sections (axial and transverse) from the Taft Formation are here assigned to Iraqia simplex Henson, a taxon restricted to the late early Aptian to basal upper Aptian (Ullastre et al, 2002;Masse, 2003;Schlagintweit et al, 2016). It has previously been recorded from the lower Aptian Taft (Schlagintweit et al, 2019) and Tirgan formations (e.g., Bucur et al, 2019). The specimen determined as Mesorbitolina parva (Douglass) by Gheiasvand et al (2019, fig.…”
Section: Taft Formation Of Central Iranmentioning
confidence: 95%
“…2H) to the late Upper Cretaceous (probably upper Maastrichtian; Cuvillier et al, 1969). It is noteworthy that previous works that place the top of the Tirgan Formation beneath the overlying Sarcheshmeh Formation within the late early Aptian based on orbitolinid foraminifera (e.g., Bucur et al, 2019) were not discussed.…”
Section: Tirgan Formation Of Northeastern Iranmentioning
confidence: 99%
“…The Tirgan Formation displays considerable lateral changes in thickness, its eastern part being 36–40 m thick (in the Artrenj and Gorgoreh localities, respectively), as compared to 780 m thick near the town of Tirgan (south‐east of Dargaz city) and 1,005 m thick in the NW Kopet‐Dagh Basin (Ghezel‐tappeh locality) (Afshar‐Harb, 1994). The age of the Tirgan Formation is latest Barremian‐Early Aptian, according to biostratigraphic data based on benthic foraminifera and ammonites (Abbasi et al, 2013; Bucur et al, 2018; Molaei et al, 2019). Although, based on the new biostratigraphic study a diachroneity is suggested for the base of the Tirgan Formation (Gheiasvand et al, 2019), so that the age in the eastern part of the Kopet‐Dagh Basin is early Aptian (Kalantari, 1969) while its age in the central part of the basin is Valanginian to Albian (Gheiasvand et al, 2019).…”
Section: Geological Settingmentioning
confidence: 99%
“…This sedimentary basin has preserved up to 8,000 m of the relatively continuous succession of deep‐marine to continental carbonate, siliciclastic, and evaporitic sediments deposited from Jurassic to Miocene times (Afshar‐Harb, 1979, 1994). Many studies have been done on the Tirgan Formation of the Kopet‐Dagh Basin with the main focus on the stratigraphy, biostratigraphy, facies, and geochemical analysis (e.g., Abbasi, Sadeghi, Hosseini Barzi, & Moussavian, 2013; Bucur, Yarahmadzahi, & Mircescu, 2018; Gheiasvand et al, 2019; Molaei, Vaziri, Raisossadat, Taherpour‐Khalil‐Abad, & Taheri, 2019; Tabatabaei, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…in the Cenomanian "Nezzazata-alveolinid assemblage zone" most likely referring to the recently described species Persiconus sarvaki Yazdi-Moghadam & Schlagintweit and O. cenomaniensis.The early-early late Aptian D.? pachymarginalis Schroeder (Fig.2B-C herein) is well known from the Taft and Tirgan formations of Central Iran (e.g.,Schlagintweit & Wilmsen, 2014;Bucur et al, 2019) and has (very rarely) been described from the Aptian of the Zagros(Hamedanian et al, 2017: pl. 1D).…”
mentioning
confidence: 99%